Growth Response of Chickens on Performance and Liver Percentage Supplemented by Miana Leaf Based Eco Enzyme in Drinking Water - Fati, Nelzi; Nilawati, Nilawati; Yulia, Eva; Malvin, Toni; Syukriani, Debby; Ramaiyulis, Ramaiyulis (Jurnal Peternakan, 2024)
The aim of the research was to determine the influence of Miana leaf (ML)-based eco-enzyme onthe  performance and liver percentage inbroilers. This research used a completely randomized design. 200-day-old broilers (DOC) were randomly divided into 4 treatments and 5 replications, with each replicate consisting of 10 chickens. The four treatments were: A (0% eco-enzyme based on ML), B (2% eco-enzyme based on ML), C (4% eco-enzyme based on ML), D (6% eco-enzyme based on ML) which is supplemented by drinking water. The parameters measured were feed consumption, average daily gain (ADG), feedconversion ratio (FCR) and liverpercentage. The results obtained showed that supplemented ML significantly (P<0,05) affected  ADG. The supplementation of ML based eco enzyme did not have a significant effect  (P>0,05) on feed consumption,  feed conversion ratio and liver percentage.  The supplementation of ML based eco enzyme could be tolerated up to 6% in drinking water of broilers.